Respostas
respondido por:
1
y = x² - 4x
S = 4 x = 4 raízes da função : (4,0) (0,0)
P = 0 x = 0
Xv = 4 + 0 / 2 = 2 ou
Xv = - b / 2a = 4 / 2 = 2
Yv = F(2) = 2² - 4 . 2
F(2) = 4 - 8
F(2) = - 4 ou
Yv = - Δ / 4a = - 16 / 4 = - 4
S = 4 x = 4 raízes da função : (4,0) (0,0)
P = 0 x = 0
Xv = 4 + 0 / 2 = 2 ou
Xv = - b / 2a = 4 / 2 = 2
Yv = F(2) = 2² - 4 . 2
F(2) = 4 - 8
F(2) = - 4 ou
Yv = - Δ / 4a = - 16 / 4 = - 4
Ilma1965:
não bate as respostas
b. S = {0,- 4} e V(2,- 4)
c. S = {0, 4} e V(2,4)
d. S = {0,- 4} e V(- 2,4)
e. S = {0,4} e V(2,- 4)
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás